Utilization of Wastewater from Vannamei Shrimp Pond for Rearing Milkfish in Keburuhan Coast Purworejo Sub-District - Djumanto, Djumanto; Ustadi, Ustadi; Rustadi, Rustadi; Triyatmo, Bambang (Aquacultura Indonesiana, 2018)
Brackish water vannamei shrimp in the village of Keburuhan, Ngombol District of Purworejo Regency is one of the shrimp aquaculture activities developed since 2010. Shrimp farming enteprises is done by local communities which use the sandy soil coated plastic sheet with an area of 1000-4500 m2. There is a positive impact by increasing the income and welfare of farmers, but give negative effects in decline of surrounding pond environment. The shrimp farmers mostly disposed of wastewater directly into the sewers or the surrounding area. The wastewater of vannamei shrimp culture contains of uneaten feed and plankton that can be utilized to grow milkfish. The aim of this study was to determine the growth and feeding preferences for milkfish culture in wastewater reservoir of vannamei culture. The study was conducted from January to April 2017 by rearing of milkfish in earthen ponds of shrimp culture in wastewater reservoir. Wastes consist of feces and uneaten feed during shrimp rearing were siphoned and flowed into ponds wastewater reservoir. Milkfish juvenile with body length ranges from 9.3 to 9.7 cm and weight ranges from 3.4 to 6.9 g was introduced into three earthen ponds of 600 m2 each, with density of 6 individual/m2 in triplicate for 70 days. During the study, milkfish juvenile were not fed, but obtained wastewater from shrimp culture ponds. The wastewater from the shrimp ponds was siphoned and piped into a waste reservoir ponds every 3 days until shrimp harvesting. Fish samples of each pond as much as 40 individuals were taken biweekly and then measured the length and weight. Fish stomach was dissected and then digestive tract was taken to observe the species of plankton consumed. The results showed that milkfish could grow well in wastewater reservoir of shrimp culture. The average daily growth rate of length and weight of milkfish reached approximately 0.11 cm/day and 0.34 g/day, respectively. The length weight relationship of milkfish showed allometric growth pattern. The food type found in the intestinal was dominated by phytoplankton. Feed was dominated by genera of phytoplankton, which reach more than 99%. The most dominant of phytoplankton were Scenedesmus sp. (34.7%), then Crucigenia sp. (20.1%), followed by Cyclotella sp. (14.6%), and Clamydomonas sp. (7.5%) next Microcystis sp. (6.7%), while the other genera less than 4.2%. Further research is needed to determine the optimum density of milkfish to utilize wastewater of shrimp culture.